Static strength of CFRP-strengthened preloaded circular concrete-filled steel tube stub columns, Part I: Experimental test. (March 2023) - Xiong, C.N.; Shao, Y.B.; Tong, L.W.; Dai, K.S.; Luo, Y.X.
Abstract: In the process of strengthening circular concrete-filled steel tube (CFST) stub columns in servicing period with carbon fiber reinforced polymer (CFRP), the CFST stub columns are generally preloaded. This study concerns the efficiency of CFRP in strengthening preloaded CFST stub columns. Thirteen specimens are designed and tested under axial compression, including two un-strengthened CFST specimens, four circular CFRP-strengthened concrete-filled steel tube (CFRP-CFST) specimens without preloading and seven preloaded CFRP-CFST specimens. The failure process, the failure mechanism, and the static strengths of the specimens, including yield strength and ultimate strength, are analyzed based on the experimental results. Improvement of the static strengths of the CFRP-strengthened specimens is discussed. The effect of preloading and CFRP layers on the static strength is investigated. The results show that preloading has certain effect on the yield strength. However, its effect on the ultimate strength is very little and it can be ignored. Increasing CFRP layers can improve the strengths of the preloaded CFST specimens effectively. Highlights: Experimental tests on preloaded CFRP-CFST stub columns were conducted. Failure mechanism of preloaded CFRP-CFST stub columns was analyzed. Effects of preloading and CFRP layers on CFRP strengthening efficiency were studied.